Analysis of labor productivity in the installation of walls with lightweight bricks in the construction project of Sudamala Resort Ubud - Krisnantara, Pande Made Agus; Indrashwara, Decky Cipta; Ariana, I Komang Agus; Nuraga, I Ketut (Privietlab, 2026)
Labor productivity is an important indicator for controlling time, cost, and quality in construction projects. The installation of lightweight brick walls requires a high level of efficiency; however, in practice, there is often a discrepancy between the actual productivity in the field and applicable standards. This study aims to analyze labor productivity in lightweight brick wall installation work and compare it with the standards set out in Regulation of the Minister of Public Works and Public Housing (Permen PUPR) Number 01 of 2022. The study was conducted on the Sudamala Resort Ubud construction project using direct observation and a work sampling approach. Observations were made for 14 working days during normal working hours to obtain data on the number of workers, effective working time, and volume of work produced. The data were analyzed to determine the productivity value and coefficient of workers, which consisted of foremen, master craftsmen, craftsmen, and laborers. The results of the study show that the average productivity of workers in the field is 18.175 m²/day for foremen, 19.123 m²/day for master craftsmen, and 18.546 m²/day for craftsmen and workers, with productivity coefficients of 0.055, 0.041, and 0.239, respectively. Compared to the standard of Permen PUPR 01 of 2022, there are differences in productivity values and coefficients in each labor category. These differences are influenced by the field conditions, workforce composition, and work implementation methods.